Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: How many solutions does equation (x^2-25)^2=x^2-10x+25 have [#permalink]
07 Feb 2014, 20:13

(x^2-25)^2=x^2-10x+25 => |x^2-25|=|x-5| Case 1: Both +ve or both negative: x^2-25 = x-5 => x^2 - x -20 = 0 => (x-5)(x+4) = 0 => x = 5, -4 Case 2: One +ve and other -ve: x^2-25 = -(x-5) = -x + 5 => x^2 + x -30 = 0 => (x+6)(x-5)= 0 => x = -6, 5

Re: How many solutions does equation (x^2-25)^2=x^2-10x+25 have [#permalink]
23 May 2014, 10:10

1

This post received KUDOS

This is a perfect example of an official GMAT question because it looks complicated but is meant to be solved solely by factoring and using the difference of squares identity. Of course one could expand the entire expression and create a mess, but GMAT writers do not expect students to go in that direction.

See the attached solution in the image.

Cheers, Dabral

Attachments

GMATClub-05232014.png [ 62 KiB | Viewed 439 times ]

Re: How many solutions does equation (x^2-25)^2=x^2-10x+25 have [#permalink]
13 Jun 2014, 07:05

@aknine

{(x+5)(x-5)}^2=(x-5)^2

At this stage, we cannot divide both sides by (x-5)^2, because that would mean ignoring the solution x=5. Instead, subtract and factor, and that would show that x=5 is also a solution.

Also, once you are at the next stage of (x+5)^2=1 there is no need expand the (x+5)^2 term, instead we can directly conclude:

x+5 = 1 or x+5=-1 which gives the remaining two solutions of x=4 and x = -6.